PERBANDINGAN TUBIFEX SP DAN CHIRONOMUS SP DALAM PAKAN TERHADAP PENINGKATAN WARNA IKAN KOMET (Carassius auratus) - Natalis, Victoria; Lukas, Ade Yulita Hesti; Djonu, Asriati (Nusa Cendana University, 2025)
A 30-day nutritional experiment was conducted at the Aquaculture Research Laboratory, Faculty of Fisheries and Marine Sciences. The study employed a Completely Randomized Design (CRD) with three experimental diets: (A) exclusive Tubifex sp. meal, (B) equal combination of Tubifex sp. and Chironomus sp. meals (1:1 ratio), and (C) exclusive Chironomus sp. meal, each replicated three times. Key performance indicators including skin pigmentation intensity, body weight gain, and linear growth were measured in goldfish (Carassius auratus). Statistical analysis revealed significant dietary effects (p<0.05) on all measured parameters. The blended diet (Treatment B) demonstrated superior efficacy, producing both the most vibrant coloration and maximal growth metrics among test groups. These findings suggest that balanced inclusion of both worm meals synergistically enhances ornamental quality and growth performance in this commercially valuable fish species. Keywords: Chironomus sp, C. auratus, Tubifex sp.